Area‐Selective Atomic Layer Deposition on Functionalized Graphene Prepared by Reversible Laser Oxidation (Adv. Mater. Interfaces 29/2022). Issue 29 (19th October 2022) - Mentel, Kamila K.; Emelianov, Aleksei V.; Philip, Anish; Johansson, Andreas; Karppinen, Maarit; Pettersson, Mika
Abstract : Area‐Selective Atomic Layer Deposition In article number 2201110, Kamila Mentel, Maarit Karppinen, Mika Pettersson, and co‐workers used laser‐induced oxidation of graphene as a surface activation tool, that guided atomic layer deposition to the pre‐defined regions. This procedure allows to deposit metal oxide on graphene without pattern placement errors, therefore, it is expected to enable improved fabrication of graphene‐based electronic devices.